2013
DOI: 10.1192/apt.bp.112.011049
|View full text |Cite
|
Sign up to set email alerts
|

Young people who cut themselves: can understanding the reasons guide the treatment?

Abstract: SummaryYoung people who cut themselves may do so for reasons that go beyond diagnosis. Relevant processes include responses to trauma, coping, emotion regulation and cultural identification. Some clinicians regard those who self-harm negatively or consider one therapeutic approach to be suitable for all. This article explores the possible mechanisms involved when young people cut themselves and discusses therapeutic approaches in the light of these. Clinicians and researchers are encouraged to refine, develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 90 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…At present, there is no definitive evidence to support any specific treatment intervention for self-harm alone (Ougrin, 2012). Preventive interventions require a stronger evidence base (Robinson et al, 2013) including more intervention studies tailored to the widely differing associated causes of self-harm (Wright et al, 2013). As shown in this review, research does not currently provide clear exposition of the associations of self-harm in young people.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…At present, there is no definitive evidence to support any specific treatment intervention for self-harm alone (Ougrin, 2012). Preventive interventions require a stronger evidence base (Robinson et al, 2013) including more intervention studies tailored to the widely differing associated causes of self-harm (Wright et al, 2013). As shown in this review, research does not currently provide clear exposition of the associations of self-harm in young people.…”
Section: Discussionmentioning
confidence: 92%
“…A systematic review of systematic reviews is a methodology that enables these to be brought together. Updating and furthering our understanding of these factors is imperative to guide the development of societal and health responses and interventions (Wright et al, 2013), given the multiplicity of areas that these could be targeted. Such areas could include prevention (Robinson et al, 2011), reduction of stigma (Naylor et al, 2009), promotion of resilience, self-efficacy and coping strategies (Mikolajczak et al, 2009;Reisner et al, 2014), interventions for depression (Middleton et al, 2005), psychosocial interventions (Corcoran et al, 2011), emergency care (Newton et al, 2010), and cultural interventions (Cervantes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics as impulsivity, poor problem-solving, hopelessness, high levels of self-criticism, affect dysregulation, difficulties in emotion regulation and coping, feelings of loss of control and detachment with consequent increased need of control, perfectionism, unhealthy care seeking and other aspects have been observed in youths presenting NSSI (Wright et al 2013), whilst many of these aspects are often reported also in those with ED (Cucchi et al 2016;Vieira et al 2016;Lavender et al 2015). Concurrent obsessive compulsive disorders, depression, personality disorders have been also observed in both ED and NSSI (Cucchi et al 2016;Wright et al 2013;Svirko and Hawton 2007;Sansone and Levitt 2002).…”
Section: Common Aspects and Factors In Ed And Nssimentioning
confidence: 99%
“…Eating disorders (ED) and non-suicidal self-injury behaviors (NSSI) are frequent disorders among adolescents and youths, with a lifetime prevalence ranging from 0.5 to 23% for ED (Smink et al 2012;Swanson et al 2011;Lock 2010;Favaro et al 2004) and from 5 to 25% for NSSI (Favaro et al 2004;Wright et al 2013). Female adolescents seem to be at higher risk to present one or both disorders than male adolescents (Brown and Kimball 2013;Wright et al 2013). Some evidence show a correlation between the two disorders as concurrent, or one preceding the other (Peterson et al 2008;Svirko and Hawton 2007;Favaro and Santonastaso 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation